CBIO-29. ACOT7 REGULATES COLONIZATION OF BREAST CANCER CELLS IN THE BRAIN BY REGULATING ENDOPLASMIC RETICULUM STRESS RESPONSE - Kanojia, Deepak (Neuro Oncol, 2017)
Colonization of cancer cells in a foreign organ is the key for establishment of metastases. To identify the genes that are responsible for colonization of breast cancer cells in the brain, we conducted an in silico analysis using a NKI dataset and identified ACOT-7 to be negatively correlated with patient survival. ACOT-7 is normally expressed in the brain and is responsible for maintaining the cellular pool of coenzyme-A by catalyzing the conversion of acyl-CoA to free fatty acid and CoA. The resulting CoA can be used for anabolic reactions. ACOT-7 was found to be overexpressed in microdissected brain metastases as compared to primary breast cancer tissues, and it was also upregulated in brain metastasis models CN34/CN34BrM2 and BT-474/BT-474BrM3. To understand the role of brain specific protein ACOT-7 in brain metastasis, ACOT-7 knockdown studies were conducted. ACOT7 knockdown in CN34Br cells reduced their ability to grow in the brain, which subsequently resulted in increased median survival by 60% in a preclinical mouse model. To understand the role of ACOT-7, we conducted a whole proteome analysis and found reduced expression of genes responsible for unfolded protein response (UPR)/Endoplasmic reticulum (ER)-stress. The results were confirmed using quantitative RT-PCR and western blotting. ACOT-7 knockdown cells also exhibited increased sensitivity to thapsigargin (an ER stress inducer). In conclusion, ACOT-7 is aberrantly expressed in brain metastases arising from breast cancer, and it regulates the ability of cells to counter ER stress. Hence unfolded protein response/ER stress proteins will be a novel therapeutic target for the treatment of breast cancer brain metastases.